D-Transposition of great arteries with severe calcific aortic stenosis in an adult patient: a rare presentation - Mishra, Prashant; Surana, Kuntal; Raut, Chaitanya; Shewale, Vijay (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2022)
The incidence of transposition of great arteries (TGA) is 31 per 100000 live births worldwide [1]. It is, however, the most common cyanotic congenital heart defect seen in neonates [2]. The arterial switch operation (ASO) performed in neonates is the treatment of choice for patients born with TGA-intact ventricular septum (IVS). In India, however, late referral of patients with TGA and IVS is common. Left ventricle (LV) retraining followed by ASO is an option in late presenting TGA-IVS [3, 4]. Atrial switch as the primary procedure is another option.